Determining Effective Lifetime of Minority Carriers in Silicon Through Modulated Free Carrier Absorption - Petursson, Karl (My University, 2017)
The minority carrier lifetime is a valuable parameter for determining the electrical properties of semiconductors. It is particularly useful in the fabrication of solar cells as minority carrier lifetime is directly related to device efficiency. Pump-probe techniques, in which a pump laser of photon energy above the bandgap energy of the material is used to excite free carrier populations while a sub-bandgap probe laser is used to monitor the change in excess carrier density have been demonstrated to be an effective, non-contact, method to measure the minority carrier lifetime, particularly well-suited for use as an in-line measurement apparatus for the solar cell manufacturing processes In this thesis a non-contact, optical, pump-probe method has been used to determine the minority carrier lifetime of float zone and Czochralski grown <100> silicon samples through measurements of modulated free carrier absorption. The equivalence between measurements performed using the transmitted part of the probe beam and those made with the reflected part have been demonstrated on bare silicon wafers, as well as measurement of effective minority carrier lifetime of a completed solar cell, demonstrating the ability of this technique to measure the effective minority carrier lifetime at any stage of the solar cell manufacturing process.
Keywords: Free Carrier Absorption